Acne e cefaleias - uma relação que não deve ser esquecida: Acne and headache - a relationship that should not be forgotten - Ribeiro Ferreira Barros, Ana Cristina Gonçalves; Baptista, Diana; Silva, Ângela; Pereira, Olga; Laranjeira, Carla (Adolescência e Saúde, 2012)
Objective: Headaches can refl ect serious pathologies, and the signs and symptoms of intracranial hypertension (ICH) indicate the need for etiological investigation. This case study describes an adolescent girl with headaches taking minocycline, a drug widely used in dermatology. Case description: A twelve-year-old female with progressively more severe headaches, nausea and vomiting, with horizontal diplopia and intermittent pulsatile tinnitus, medicated with oral minocycline and topical adapalene for acne over the previous six weeks. An objective examination revealed abduction limitation of the right eye and symmetrical non-infl ammatory bilateral papilledema. The imaging study excluded intracranial mass and intracranial pressure at the lumbar puncture, higher than 50 cm of water. The Epstein-Barr virus was the only positive fi nding in the infectious examination of the cerebrospinal fl uid. After switching to acetazolamide and taking her off minocycline, the symptoms improved. Remark: Due to the prevalence of acne among adolescents and the prescription of tetracyclines for its treatment, it is vital to be alert for signs of ICH, with rapid treatment preventing permanent loss of sight.